2016
DOI: 10.1186/s12867-015-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of four non-coding Y RNAs from Chinese hamster cells: identification, molecular dynamics simulations and DNA replication initiation assays

Abstract: BackgroundThe genes coding for Y RNAs are evolutionarily conserved in vertebrates. These non-coding RNAs are essential for the initiation of chromosomal DNA replication in vertebrate cells. However thus far, no information is available about Y RNAs in Chinese hamster cells, which have already been used to detect replication origins and alternative DNA structures around these sites. Here, we report the gene sequences and predicted structural characteristics of the Chinese hamster Y RNAs, and analyze their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For example, He et al reported upregulated SALL4 in esophageal squamous cell carcinoma tissues 29 . Similarly, Chen et al found overexpression of SALL4 in breast cancer cells 30 . Consistent with their findings, we observed that SALL4 was elevated in osteosarcoma tissues and cell lines compared to corresponding normal tissues and cells.…”
Section: Discussionmentioning
confidence: 80%
“…For example, He et al reported upregulated SALL4 in esophageal squamous cell carcinoma tissues 29 . Similarly, Chen et al found overexpression of SALL4 in breast cancer cells 30 . Consistent with their findings, we observed that SALL4 was elevated in osteosarcoma tissues and cell lines compared to corresponding normal tissues and cells.…”
Section: Discussionmentioning
confidence: 80%
“…The nucleophosmin 1 gene is located on chromosome 5q35 and consists of 12 exons [ 16 ]. It encodes a multifunctional protein comprised of 294 amino acids (35–40 kDa).…”
Section: Nucleophosmin 1 Structurementioning
confidence: 99%
“…The conserved N-terminus of NPM1 has two nuclear exporter signals (NES) that facilitate movement from the nucleoplasm to cytoplasm in association with a nuclear exporter protein exportin 1/chromosomal region maintenance 1 XPO1/CRM1 and has a significant role in binding a wide range of proteins [ 18 ]. Post translational modification also influences cellular movement via self-oligomerisation of NPM1 to pentameric form promoting export from the nucleolus with phosphorylation controlling monomerization and a return to nucleolar localisation [ 16 , 19 ]. Within the central domain two nuclear localisation signals (NLS) lead to movement from cytoplasm to nucleoplasm whilst a C-terminus domain with two nucleolar localisation signals (NoLS) containing highly conserved tryptophans at positions 288 and 290 plays a crucial role in localising NPM1 back to the nucleolus [ 20 ].…”
Section: Nucleophosmin 1 Structurementioning
confidence: 99%
“…Mutating the endonuclease motif also causes one log lower viral growth in the eye and the trigeminal ganglia of an ocular mouse model, indicating that the effect of U L 24 endonuclease function is involved in dissemination of HSV-1 from the eye to the ganglia in vivo [ 709 ]. Another nucleolar component that is dispersed due to the endonuclease function of U L 24 is the B23 nucleolar protein [ 710 ], which is a multifunctional protein that participates in ribosome biogenesis, mRNA processing, chromatin remodeling, and maintains genome stability [ 711 ]. U L 24 also mediates nuclear egress of HSV-1 nucleocapsids and this effect most likely occurs through the abovementioned effect of U L 24 on dispersion of nucleolar proteins [ 712 ].…”
Section: Virion Morphogenesis Egress Cell-to-cell Spread and Homentioning
confidence: 99%